Molecular Analysis of the Enteric Protozoa Associated with Acute Diarrhea in Hospitalized Children - Boughattas, Sonia; Behnke, Jerzy M.; Al-Ansari, Khalid; Sharma, Aarti; Abu-Alainin, Wafa; Al-Thani, Asma; Abu-Madi, Marawan A. (Frontiers in Cellular and Infection Microbiology, 2017)
Paediatric diarrhea is a common cause of death among children under 5 years of age. In the current study, we investigated the frequency of intestinal parasites among 580 paediatric patients with chronic diarrhoea. Parasitic protozoa (all species combined) were detected by molecular tools in 22.9% of the children and the most common parasite was Cryptosporidium spp. (15.1%). Blastocystis hominis was detected in 4.7%, Dientamoeba fragilis in 4%, Giardia duodenalis in 1.7% and Entamoeba histolytica in 0.17%. Protozoan infections were observed among all regional groups, but prevalence was highest among Qatari subjects and during the winter season. Typing of Cryptosporidium spp. revealed a predominance of Cryptosporidium parvum in 92% of cases with mostly the IIdA20G1 subtype. Subtypes IIdA19G2, IIdA18G2, IIdA18G1, IIdA17G1, IIdA16G1 and IIdA14G1 were also detected. For Cryptosporidium hominis, IbA10G2 and IbA9G3 subtypes were identified. This study provides supplementary information for implementing prevention and control strategies to reduce the burden of these paediatric protozoan infections. Further analyses are required to better understand the local epidemiology and transmission of Cryptosporidium spp. in Qatar.